2020
DOI: 10.3390/nu12061880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creatine Supplementation during Resistance Training Sessions in Physically Active Young Adults

Abstract: The purpose was to examine the effects of creatine supplementation during resistance training sessions on skeletal muscle mass and exercise performance in physically active young adults. Twenty-two participants were randomized to supplement with creatine (CR: n = 13, 26 ± 4 yrs; 0.0055 g·kg−1 post training set) or placebo (PLA: n = 9, 26 ± 5 yrs; 0.0055 g·kg−1 post training set) during six weeks of resistance training (18 sets per training session; five days per week). Prior to and following training and suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
(34 reference statements)
1
27
0
5
Order By: Relevance
“…More recently, a study examined the effects of Cr supplementation ingested throughout exercise training. Specifically, Mills et al [ 55 ] analysed the effects of intra-set Cr supplementation during resistance training sessions on skeletal muscle mass and exercise performance in physically active young adults, which engaged in a structured resistance training program ( Table 1 ). Twenty-two participants were randomised in a double-blind placebo-controlled design to a group supplemented with Cr (0.0055 g·kg −1 following each training set, totalling 18 sets per session) or a group supplemented with a placebo (maltodextrin, 0.0055 g·kg −1 following each training set, totalling 18 sets per session) during six weeks of RT performed five days per week.…”
Section: Creatine Supplementation Pre- During- or Post-workout: The Evidencementioning
confidence: 99%
“…More recently, a study examined the effects of Cr supplementation ingested throughout exercise training. Specifically, Mills et al [ 55 ] analysed the effects of intra-set Cr supplementation during resistance training sessions on skeletal muscle mass and exercise performance in physically active young adults, which engaged in a structured resistance training program ( Table 1 ). Twenty-two participants were randomised in a double-blind placebo-controlled design to a group supplemented with Cr (0.0055 g·kg −1 following each training set, totalling 18 sets per session) or a group supplemented with a placebo (maltodextrin, 0.0055 g·kg −1 following each training set, totalling 18 sets per session) during six weeks of RT performed five days per week.…”
Section: Creatine Supplementation Pre- During- or Post-workout: The Evidencementioning
confidence: 99%
“…Studies on supplementation by creatinine show positive effect on performances and strength in duration of short-term maximum exercising intensity measured in one-repetition maximum and effect on mscle endurance and speed (Becque, Lochmann, & Melrose, 2000;Volek & Rawson, 2004;Vandenberghe, 1997;Vandenberghe et al, 1997;Volek & Rawson, 2004). Increased strength on bench press after CR supplementation was mentioned in some of the papers (Amirsasan et al, 2018;Vilar-Neto et al, 2018;Bjelica et al, 2020;Mills et al, 2020). Other research demonstrated similar improvements in bench press performances (Camic et al, 2014;Kilduff et al, 2002;Rawson & Volek, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…In four papers the research was performed on around 133 male participants istraživanja (Amirsasan, Nabilpour, Pourraze, Curby, 2018;Wang, Fang, Lee, & Yang, 2018;Vilar-Neto et al, 2018;Bjelica et al, 2020), in two papers research participants were 54 women. In the paper by Mills et al (2020) it was combination of male and female participants. All the participants used creatinine monohydrate as supplement to regular diet, in addition to activity.…”
Section: Resultsmentioning
confidence: 99%
“…Istraživanjem je obuhvaćeno oko 133 ispitanika muškog pola u četiri istraživanja (Amirsasan, Nabilpour, Pourraze, Curby, 2018;Wang, Fang, Lee, & Yang, 2018;Vilar-Neto et al, 2018;Bjelica et al, 2020), u dva istraživanja 54 ispitanice ženskog pola. U radu Mills et al (2020) radilo se o kombinaciji ispitanika muškog i ženskog pola. Svi ispitanici su pored aktivnosti koristili kreatin monohidrat kao vid dodatne suplementacije pored redovne ishrane.…”
Section: Rezultatiunclassified
“…Studije o suplementaciji kreatinom pokazuju pozitivan učinak na performanse i snagu za vrijeme kratkotrajnog, maksimalnog intenziteta vježbe, mjerene u toku jednog maksimalnog ponavljanja, učinak na mišićnu izdržljivost i brzinu (Becque, Lochmann, & Melrose, 2000;Volek & Rawson, 2004;Vandenberghe, 1997;Vandenberghe et al, 1997;Volek & Rawson, 2004). Povećanje snage u bench press-u nakon konzumacije CR je zabilježeno u nekim od izdvojenih radova (Amirsasan et al, 2018;Vilar-Neto et al, 2018;Bjelica et al, 2020;Mills et al, 2020). Ostala istraživanja su demonstrirala slična poboljšanja u bench press-u performanse (Camic et al, 2014;Kilduff et al, 2002;Rawson & Volek, 2003).…”
Section: Diskusijaunclassified